Squat lobsters of the superfamily Chirostyloidea (Decapoda: Anomura) from seamounts on the Nishi-Shichito and Mariana ridges, North-West Pacific off Japan, with descriptions of two new species - Komai, Tomoyuki; Tsuchida, Shinji; Fujiwara, Yoshihiro (Zootaxa, 2023)
A small collection of chirostyloid squat lobsters was studied, collected from seamounts on the Nishi-Shichito, West Mariana, and Central Mariana ridges, which have been collectively designated as marine protected areas (MPAs) of Japan. Specimens were collected using a remotely operated vehicle (ROV). Four species belonging to three families were identified, of which two are new to science: Uroptychus medius n. sp. (Chirostylidae), Eumunida smithii Henderson, 1885, E. treguieri de Saint Laurent & Poupin, 1996 (Eumunididae), and Sternostylus spiniger n. sp. (Sternostylidae). Identities of those species were assessed using an integrative approach based on morphological comparison and genetic analysis of two mitochondrial markers (COI and 16S rRNA genes). The two species of Eumunida represent the first records from Japanese waters.